ISSUES OF RAISING THE TAX COMPLIANCE CULTURE - Ochilov Adkham Muzaffarovich (American Journals, 2024)
This research article is devoted to the consideration of the issues of raising the tax compliance culture. By determining the most advanced practices, highlighting the impact of specific legislative changes, as well as making recommendations, this study contributes to ongoing improvements in optimizing tax systems globally. The research findings may be particularly relevant to practitioners seeking to strike a balance between revenue generation objectives and fostering a tax environment that encourages voluntary compliance.
Keywords: Tax obligations, taxes, levies, tax evasion, taxation.